A DESCRIPTIVE COST ANALYSIS OF HOSPITALISATIONS AT A DISTRICT HOSPITAL FOLLOWING INSULIN DISCONTINUATION - Tan, Yi Jing; Puah, Soo Huan; Rasidi, Nur Iffah Illani Mohamed; Ibrahim, Muhammad Faris Nazmi Mohammad; Ikhiwan, Nur Syahiidah Mohamad; Majid, Suriani; Kamarudin, Azyan; Ismail, Nur Amalina; Karim, Siti Ratna Dewi Abdul; Shaudin, Nurul Nadiah; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION A nationwide shortage of human insulin in Ministry of Health (MOH) facilities has forced primary care clinicians to delay initiation, de-intensify, or temporarily discontinue insulin therapy in patients with Type 2 Diabetes (T2D), prioritising oral glucose-lowering drugs. Reduced insulin use may have compromised glycaemic control, increasing the risk of acute complications. This study aims to estimate the direct medical costs of hospitalisations for acute hyperglycaemic events in a district hospital. METHODOLOGY Adult patients admitted to Hospital Jempol with acute T2D complications – uncontrolled diabetes (UD), diabetic ketoacidosis (DKA), and hyperosmolar hyperglycaemic state – linked to insulin discontinuation from September 1, 2024, to February 28, 2025, were identified. An activity-based micro-costing approach was applied to quantify resource utilisation through medical records review. Cost components included ward stays, diagnostic procedures, laboratory investigations, pharmaceuticals, and consumables. Unit costs were sourced locally. Mean per-event costs were estimated for each complication type and expressed in 2025 Malayan Ringgits (RM). RESULT Twelve patients (mean age ± SD: 62.8±8.3) with hospitalisations temporally linked to insulin discontinuations were identified, including 10 UD and 2 DKA cases, with total costs of RM61,877. The median length of stay (LOS) for UD was 4 days (range: 1-11), and it was longer for DKA (6-11 days). The mean cost per UD admission was RM3,637 ± 2,200 (RM1,763-8,753), while DKA admissions were more costly (RM6,108-19,398). Higher costs are correlated with longer stays. Daily mean costs were RM918 (±309) for UD, and RM1,391±527 for DKA. Procedures and laboratory investigations were the largest cost drivers (62.3%), followed by ward stays (25.2%), and inpatient drugs/consumables (12.4%). CONCLUSION Inpatient management of acute hyperglycaemic events is resource intensive. This study provides unit cost estimates for UD and DKA admissions, which, when combined with nationwide LOS data, can assess the financial impact of the insulin shortage on the MOH.